Kepemimpinan Sekolah Berbasis Nilai dan Sistem: Strategi Mengelola Perubahan Organisasi - Sarpala Hasan; Ruswan; Agustina Rahmi (PT. Hasba Edukasi Mandiri, 2025)
The Society 5.0 era requires educational institutions to adapt quickly and strategically to the challenges and opportunities brought by technological advancements and artificial intelligence. This study aims to examine the forms and practices of school leadership based on values and systems in managing organizational change in education. Using a library research method, this study analyzes recent literature on transformational leadership, educational supervision, curriculum development, digital technology integration, and teachers’ digital literacy. The findings indicate that effective leadership integrates local and religious values—such as the Murakata philosophy and Islamic principles—with adaptive, collaborative, and technology-based management systems. Strategies involving supervision, curriculum adjustment, learning innovation, and teacher empowerment significantly contribute to improving educational quality. In conclusion, value- and system-based leadership is a strategic approach capable of responding to digital era challenges while positioning schools as centers of innovation and character building.